A Three-Dimensional Multiscale Model for Gas Exchange in Fruit(1)([C])([W])([OA]) - Ho, Quang Tri (American Society of Plant Biologists, 2011)
Respiration of bulky plant organs such as roots, tubers, stems, seeds, and fruit depends very much on oxygen (O(2)) availability and often follows a Michaelis-Menten-like response. A multiscale model is presented to calculate gas exchange in plants using the microscale geometry of the tissue, or vice versa, local concentrations in the cells from macroscopic gas concentration profiles. This approach provides a computationally feasible and accurate analysis of cell metabolism in any plant organ during hypoxia and anoxia. The predicted O(2) and carbon dioxide (CO(2)) partial pressure profiles compared very well with experimental data, thereby validating the multiscale model. The important microscale geometrical features are the shape, size, and three-dimensional connectivity of cells and air spaces. It was demonstrated that the gas-exchange properties of the cell wall and cell membrane have little effect on the cellular gas exchange of apple (Malus × domestica) parenchyma tissue. The analysis clearly confirmed that cells are an additional route for CO(2) transport, while for O(2) the intercellular spaces are the main diffusion route. The simulation results also showed that the local gas concentration gradients were steeper in the cells than in the surrounding air spaces. Therefore, to analyze the cellular metabolism under hypoxic and anoxic conditions, the microscale model is required to calculate the correct intracellular concentrations. Understanding the O(2) response of plants and plant organs thus not only requires knowledge of external conditions, dimensions, gas-exchange properties of the tissues, and cellular respiration kinetics but also of microstructure.